Non-fixed working hours in the context of globalisation: the impact of international trends on national legislation and employers' practices - Oleg M. YAROSHENKO; Olena SEREDA; Volodymyr HARASHCHUK; Leonid MOHILEVSKYL; Alla YUSHKO (Revista Jurídica Portucalense, 2024)
Globalisation and information technology are having an active impact on various spheres of society, from the economic sphere to labour relations. The direct impact on the labour sphere can be seen in the change in trends in the definition of working hours, as today there are more opportunities for compromise between employees and employers on setting working hours and agreeing on the possibility of non-fixed working hours. This has resulted in flexible working arrangements. This is what makes this study relevant. The purpose of this study is to identify the benefits of non-fixed working hours and to analyse the challenges faced by participants in labour relations when establishing flexible working hours in the context of globalisation. It is important to study global patterns and trends in the introduction of flexible working hours at the international level, taking into account international regulations. It is also advisable to assess the impact of international recommendations on the formation of national labour legislation in the framework of non-fixed working hours. In order to achieve this purpose, a number of methods of scientific knowledge were used, such as systematic analysis, synthesis, formal legal method, dialectical method and method of analysis of regulatory documents. The findings will serve as a basis for further research in this area and will contribute to the development of recommendations for adapting the current legislation to the realities of today, the rapid development of information technology and globalisation.